2013
DOI: 10.15381/rivep.v14i1.1596
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalencia De La Dirofilariosis Y Ehrlichiosis Canina en Tres Distritos De Lima

Abstract: Canine Heartworm Disease is a parasitic disease caused by the nematode Dirofilaria immitis. The adult forms are found mainly in the pulmonary arteries and the right heart of canids. This nematode is transmitted by intermediate hosts which are blood suckling mosquitoes. Canine Ehrlichiosis is a disease of domestic and wild canids, caused by the rickettsia Ehrlichia canis, that infects mononuclear cells. This microorganism is transmitted by an arthropod vector, the brown dog-tick Rhipicephalus sanguineus. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
3
0
7
Order By: Relevance
“…In Adrianzén (2002) demonstrated a mean prevalence of 4.4% in three districts of Lima (Chorrillos, La Molina and San Juan de Miraflores). In Adrianzén et al (2003) reported the prevalence for three rural districts near Lima on the shores of the Lurin river: 12.5% for Cieneguilla, 7.5% for Lurin, and 2% for Pachacamac. In the most recent study from Corimanya et al (2004) reported a 5.5% prevalence in the district of San Juan de Lurigancho near the Rimac river, which crosses the city of Lima.…”
Section: Resultsmentioning
confidence: 99%
“…In Adrianzén (2002) demonstrated a mean prevalence of 4.4% in three districts of Lima (Chorrillos, La Molina and San Juan de Miraflores). In Adrianzén et al (2003) reported the prevalence for three rural districts near Lima on the shores of the Lurin river: 12.5% for Cieneguilla, 7.5% for Lurin, and 2% for Pachacamac. In the most recent study from Corimanya et al (2004) reported a 5.5% prevalence in the district of San Juan de Lurigancho near the Rimac river, which crosses the city of Lima.…”
Section: Resultsmentioning
confidence: 99%
“…Esto implica la necesidad de evaluar este posible factor asociado en cada población particular. También debe precisarse que los análisis estadísticos no mostraron diferencias significativas en la comparación de la seroprevalencia de infección con la variable de sexo, por lo que las diferencias expuestas no permiten consolidar una hipótesis causal; esto es similar al encontrado en el estudio de Sainz y colaboradores, y contrasta con el estudio de Adrianzen y colaboradores (11,25).…”
Section: Discussionunclassified
“…Se consideró como animal positivo aquel que presentó sintomatología (depresión, anorexia, fiebre alta, epistaxis, petequias, linfadenomegalia, problemas oculares, disnea, dolor articular) y hematología (trombocitopenia, leucopenia, pancitopenia y anemia) compatible con Ehrlichiosis, y que, además, la muestra de sangre resultó serológicamente positiva a E. canis con el kit comercial de ELISA Snap® 3Dx® (IDEXX Labs), prueba que tiene una especificidad de 100% y una sensibilidad de 95% (Adrianzén, 2003). Así mismo, se consideró como negativo a todo animal diagnosticado o tratado por cualquier enfermedad diferente a Ehrlichiosis.…”
Section: Materiales Y Métodosunclassified